Potassium fractions in soil and simple K balance in long-term fertilising experiments - Jiří Balík; Martin Kulhánek; Jindřich Černý; Ondřej Sedlář; Pavel Suran (Soil and Water Research, 2020)
Experiments were used to determine the potassium release from the non-exchangeable K (Kne) forms that are involved in plant nutrition and which replenish the pool of available K. Long-term stationary field experiments with different fertilisation systems (organic: farmyard manure, sewage sludge, straw; mineral: NPK, N) were carried out to study the potassium balance and the K content changes in the topsoil (0-30 cm) and subsoil (30-60 cm). The trials were located at three sites with different soil-climatic conditions. The following crops were rotated within the trial: potatoes (maize) - winter wheat - spring barley. All three crops were grown each year over 21 years. Positive correlations between the contents of the available K in the topsoil and the potassium balance (K inputs - K outputs) were observed. There were no statistically significant differences among the treatments. Depending on the soil properties, the ratio of non-exchangeable K (Kne) was 12-37% of the values obtained via the aqua regia extraction. Depending on the site, the amount released from the Kne forms to the available K form was 46-69 kg K/ha/ year. The use of K from the farmyard manure varied from 7.4% up to 25%. Due to the low K content in the sewage sludge, the long-term fertilisation with sludge may only lead to the depletion of the available K in the soil, similar to the sole N mineral fertilisation.